Exploring the Fecal Microbial Composition and Metagenomic Functional Capacities Associated With Feed Efficiency in Commercial DLY Pigs - Quan, Jianping; Cai, Gengyuan; Yang, Ming; Zeng, Zhonghua; Ding, Rongrong; Wang, Xingwang; Zhuang, Zhanwei; Zhou, Shenping; Li, Shaoyun; Yang, Huaqiang; Li, Zicong; Zheng, Enqin; et al. (Frontiers in Microbiology, 2019)
Gut microbiota has indispensable roles in nutrient digestion and energy harvesting, especially in processing the indigestible components of dietary polysaccharides. Searching for the microbial taxa and functional capacity of the gut microbiome associated with feed efficiency can provide important knowledge to increase profitability and sustainability of the swine industry. In the current study, we performed a comparative analysis of the fecal microbiota in 50 commercial Duroc × (Landrace×Yorkshire) (DLY) pigs with polarizing feed efficiency (FE) using 16S rRNA gene sequencing and shotgun metagenomic sequencing. There was a different microbial community structure in the fecal microbiota of pigs with different FE. Random forest analysis identified 24 OTUs as potential biomarkers to improve swine FE. Multiple comparison analysis detected 8 OTUs with a significant difference or tendency toward a difference between high- and low-FE pigs (P < 0.01, q < 0.1). The high-FE pigs had a greater abundance of OTUs that were from the Lachnospiraceae and Prevotellaceae families and the Escherichia-Shigella and Streptococcus genera than low-FE pigs. A sub-species Streptococcus gallolyticus subsp. gallolyticus could be an important candidate for improving FE. The functional capacity analysis found 18 KEGG pathways and CAZy EC activities that were different between high- and low-FE pigs. The fecal microbiota in high FE pigs have greater functional capacity to degrade dietary cellulose, polysaccharides, and protein and may have a greater abundance of microbes that can promote intestinal health. These results provided insights for improving porcine feed efficiency through modulating the gut microbiome.